Assessing the Efficiency of Inoculation Methods for Mass Propagation of Heterorhabditis indica in Various Hosts - S. Manochaya,; Krishnaveni Ramakrishna, (The Bioscan, 2025)
Mass cultivation for large-scale pest control is essential to harness the potential of Heterorhabditis indica. In the present study, the Mortality rate of different host and infectivity of H. indica were tested against several test hosts, namely Galleria mellonella larvae (GML), Bombyx mori larvae (BML), Bombyx mori pupae (BMP), Philosamiaricini larvae (PRL), and Philosamiaricini pupae (PRP). The highest constant infectivity percentage was recorded for the PRP and BML. At the 72-hour interval, the spread plate method showed the highest infectivity percentage for the PRP. It significantly decreased at the 96-hour interval due to possible temporal changes in nematode-host interactions. Mortality analysis confirmed the significant effect of inoculation method and host type on H. indica effectiveness. Notably, the immersion method showed the lowest infectivity percentages for BML and BMP at the 72-hour interval. The spread method induced the highest mortality for H. indica, emphasizing its initial efficacy. However, at the 96-hour interval, the spread method outperformed the other methods, achieving the highest mortality in most hosts. The present study findings will help develop cost-effective and sustainable strategies for the mass cultivation of entomopathogenic nematodes (H. indica), promoting their broader adoption as eco-friendly alternatives for pest management in agriculture.